2015
DOI: 10.1038/ncomms8370
|View full text |Cite
|
Sign up to set email alerts
|

Temporal tweezing of light through the trapping and manipulation of temporal cavity solitons

Abstract: Optical tweezers use laser light to trap and move microscopic particles in space. Here we demonstrate a similar control over ultrashort light pulses, but in time. Our experiment involves temporal cavity solitons that are stored in a passive loop of optical fibre pumped by a continuous wave 'holding' laser beam. The cavity solitons are trapped into specific time slots through a phase modulation of the holding beam, and moved around in time by manipulating the phase profile. We report both continuous and discret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
162
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(168 citation statements)
references
References 44 publications
6
162
0
Order By: Relevance
“…Additionally, our work and other theoretical work 34,36 suggests that it may be possible to use a mode crossing or a bichromatic pump to generate a seed crystal for creating complex, custom soliton trains, which could be populated through the use of a pulsed pump laser. Potential applications of storage and manipulation of solitons in nonlinear resonators have attracted considerable interest [13][14][15][16]26,40 , and soliton crystals in monolithic Kerr resonators present a possible mechanism for chip-integrated optical data storage and manipulation which exploits the enormous degeneracy of soliton crystal configuration space and is stable to perturbations and local interactions. Finally, the mechanism we present here for soliton-soliton interactions has implications for periodic systems in any context in which nonlinearity and dispersion or diffraction contribute significantly to the dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our work and other theoretical work 34,36 suggests that it may be possible to use a mode crossing or a bichromatic pump to generate a seed crystal for creating complex, custom soliton trains, which could be populated through the use of a pulsed pump laser. Potential applications of storage and manipulation of solitons in nonlinear resonators have attracted considerable interest [13][14][15][16]26,40 , and soliton crystals in monolithic Kerr resonators present a possible mechanism for chip-integrated optical data storage and manipulation which exploits the enormous degeneracy of soliton crystal configuration space and is stable to perturbations and local interactions. Finally, the mechanism we present here for soliton-soliton interactions has implications for periodic systems in any context in which nonlinearity and dispersion or diffraction contribute significantly to the dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Formally equivalent to monolithic Kerr resonators are lower repetition-rate fiber-loop resonators, where generation and control of soliton ensembles has recently been explored experimentally [13][14][15][16] . These experiments were preceded by theoretical studies of soliton interactions and ensembles of solitons in quasi-CW-pumped fiber-ring resonators [17][18][19] , where an analogy between soliton ensembles and the states of matter was introduced.…”
mentioning
confidence: 99%
“…However, while the mode dispersion profile Δω − μ is determined entirely by the resonator geometry and the dielectric material properties, the soliton repetition rate ω r depends upon frequency offsets between the pump and the soliton spectral maximum. Defining this offset as Ω, the repetition frequency is given by the following equation [26,27]:…”
mentioning
confidence: 99%
“…As a result, they are different from mode locked lasers [79] and do not require two point locking for their stabilization [80][81][82]. Fiber loop can support a large number of non-interacting pulses that can be individually addressed [83][84][85] while microresonators also support multiple non-interacting pulses [86]. It is possible to control mode locking by modulation of the pump in both fiber cavities [87] and microcavities [88].…”
Section: Resonant Oscillationmentioning
confidence: 99%
“…The parametric seedling or injection locking of the frequency combs can be used for improvement of their stability as well as for achieving low frequency phase noise. A relevant development took place in studies of fiber loop cavity solitons where it was shown that modulated pump can be used to control the position of light pulses [84]. To reduce the fluctuations of the repetition rate of the frequency comb it was suggested to take advantage of the injection locking properties of the Kerr frequency comb oscillator and create an opto-electronic oscillator that involves an active Kerr comb oscillator as a part of the optical loop of the opto-electronic circuit [155].…”
Section: Resonant Four Wave Mixing and Multi-chromatic Pumpingmentioning
confidence: 99%